Exploding power: a statewide review of lithium battery related burns - Jason Diab; Justine O’Hara; Andrea-Issler Fisher; Erik La Hei; Robert Gates; John Vandervord; Andrew JA Holland; Peter K Maitz AM (Australasian Journal of Plastic Surgery)
**Introduction**: With the increase of lithium battery devices, including electronic cigarettes and battery power banks, there has been a steady rise in burn injuries secondary to device malfunction. These devices may cause chemical or flame burns. Our aim was to identify and classify epidemiological trends of explosions from lithium battery devices across the state of New South Wales (NSW), Australia.